2022
DOI: 10.1038/s41467-022-35679-3
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency synthetic apomixis in hybrid rice

Abstract: Introducing asexual reproduction through seeds – apomixis – into crop species could revolutionize agriculture by allowing F1 hybrids with enhanced yield and stability to be clonally propagated. Engineering synthetic apomixis has proven feasible in inbred rice through the inactivation of three genes (MiMe), which results in the conversion of meiosis into mitosis in a line ectopically expressing the BABYBOOM1 (BBM1) parthenogenetic trigger in egg cells. However, only 10–30% of the seeds are clonal. Here, we show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…By contrast, in Arabidopsis, embryogenesis was not found to be dependent on the male allele expression of AtBBM ; instead AtBBM was expressed exclusively in female maternal tissues before fertilization, and from both parental alleles in zygotes (Chen et al ., 2022). Moreover, whereas Os BBM1 expression in the egg cell induces parthenogenesis at frequencies as high as 30% in rice (Khanday et al ., 2019) or even > 95% (Vernet et al ., 2022), At BBM expression in dicots results in very low frequencies of parthenogenesis (< 1.5%) (Chen et al ., 2022). These contrasting observations indicate important differences between monocot and dicot plants, both in the regulation of BBM gene expression and in the roles of the parental genomes, for the initiation of ZE.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, in Arabidopsis, embryogenesis was not found to be dependent on the male allele expression of AtBBM ; instead AtBBM was expressed exclusively in female maternal tissues before fertilization, and from both parental alleles in zygotes (Chen et al ., 2022). Moreover, whereas Os BBM1 expression in the egg cell induces parthenogenesis at frequencies as high as 30% in rice (Khanday et al ., 2019) or even > 95% (Vernet et al ., 2022), At BBM expression in dicots results in very low frequencies of parthenogenesis (< 1.5%) (Chen et al ., 2022). These contrasting observations indicate important differences between monocot and dicot plants, both in the regulation of BBM gene expression and in the roles of the parental genomes, for the initiation of ZE.…”
Section: Discussionmentioning
confidence: 99%
“…In rice, simultaneous silencing of three meiosis‐related genes, SPO11‐1 , REC8 , and OSD1 , induced the transition from meiotic to mitotic processes in oocytes (Mieulet et al, 2016). Editing the meiosis‐ or fertilization‐related genes SPO11‐1 ‐ REC8 ‐ OSD1 or REC8 ‐ PAIR1 ‐ OSD1 ‐ MTL achieved apomixis in hybrid rice, as did simultaneously inducing the MiMe mutation via ectopic expression of OsBBM1 or OsBBM4 in the oocyte (Wang et al, 2019; Vernet et al, 2022; Wei et al, 2023). Recently, specific expression of the dandelion PAR in the MiMe system generated apomictic materials with high seed‐setting rates throughout successive generations (Song et al, 2023).…”
Section: The Development Of One‐line Rice Breedingmentioning
confidence: 99%
“…BABY BOOM (BBM), an AP2 transcription factor family protein, can initiate maternal parthenogenic embryogenesis without fertilization and leads to haploid formation in rice, maize, millet and Arabidopsis [ 15–18 ]. By combining a Meiosis instead of Mitosis ( MiMe ) system with BBM , researchers have shown that hybrid vigor can be efficiently fixed across generations through synthetic apomixis in rice [ 19 , 20 ]. However, ectopic expression of the BBM gene in egg cells is a prerequisite, so BBM- mediated parthenogenic haploids are transgenic and have limited application in plant breeding.…”
Section: Introductionmentioning
confidence: 99%